HASIL KELUARAN PENANGANAN SECARA KONSERVATIF DENGAN MENGGUNAKAN CASTING PADA FRAKTUR DISTAL RADIUS DI RS SARDJITO YOGYAKARTA - , Adam Moeljono, Rahadyan Magetsari., PhD., SpOT, FICS ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Introduction : Distal radius fracture is a common fracture approximately one sixth of all emergency cases in orthopaedic setting. In Indonesia generally and in Yogyakarta typically , these kinds of fracture are treated conservatively due to social economic condition, risk of operation, and also low functional demand. Method : Crossed sectional study. All patients met inclusion criteria such as single trauma, closed fracture, were recorded with range of age 13-80 years old (n=61) which were treated conservatively using Long Arm Cast. X ray pre and post reduction were noted, all were home visited (range of time post removal casting 4 â 18 months). Quick DASH as subjective perceived patients score were noted, MAYO wrist score which consist of pain, range of movement, grip strength, and return to work, also VAS (Visual Analogue Score). Univariate analysis were performed to analyze factors that correlates with the outcome. Results : Patients with distal radius fracture (n=61), mean age = 49,48 y.o. Performed closed reduction and average time of immobilization 3,46 weeks (range 2-12 weeks). From age, degree of severity and time of immobilization,criteria, only the degree of severity has stastically positive significant with subjective Quick DASH score (p=0,005) and VAS (p=0,001). Analysis study also showed that acceptability of post reduction palmar tilt correlated with Quick DASH score (p=0.025). Discussion : In this study, outcome of distal radius fracture correlated with degree of severity and also acceptability of post reduction palmar tilt. Keyword : distal radius fracture, degree of severity, palmar tilt, subjective Quick DASH score, objective MAYO wrist score, VAS